DETERMINANT FACTORS OF UNDERNUTRITION IN PETOAHA VILLAGE: PATH ANALYSIS: Path analysis of determinants of undernutrition - Fitri Rachmillah Fadmi; La Djabo Buton (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2020)
Background: Nutrition is still a public health problem in Indonesia. Good nutritional intake cannot be provided by children, because of the mother's knowledge, family income, and nutritional intake. Analysis of the factors that influence nutrition in children under five in Petoaha Village. Methods:This type of research is an analytic observational with cross-sectional study design. The population and sample in this study were under nutrition data in Petoaha Village. Results:The results of the path analysis show that the model fits the data with a value of RMSEA = 0.000 <0.10. Furthermore, based on the pathway with the estimation model and the t calculation shows that four factors are interrelated based on the tcalculation> 1.96, namely between income and under nutrition getting tcalculation n = 3.25; knowledge by under nutrition obtained tcalculation = 5.06; knowledge of nutritional intake was obtained by tcalculation = 2.10 and malnutrition intake, tcalculation = 2.16. Conclusion: It is hoped that it can become an information reference for policymakers in implementing preventive and promotive efforts from an early age to the community in overcoming under nutrition.